World development report 2005 a better investment climate for everyone. (Washington, D.C. World Bank ; Oxford Oxford University Press, 2004)
This annual report released by the World Bank draws on surveys of over 30,0000 firms in 53 developing countries, along with various country case studies sponsored by the World Bank. Released in September 2004, the 288- page report highlights opportuni ties to improve its investment climates by expanding the opportunities and incentives for firms of all types.
Keywords: Economic development; International economic relations; Electronic books